Prescribing Patterns of Antibiotics Among The Pediatric Patients Attended The Outpatient Departments of The Tertiary Level Hospitals in Nigeria: A Cross-Sectional Study - Aminu, Uwais; Ishaq, Abdullahi; Rummana, Shahrukh; BakiBillah, Abul Hasan (Health Nexus, 2023)
Rationality analysis of the prescribing pattern of antibiotics for pediatric patients can help to point towards irrationality and can make a consensus among physicians for rational prescribing. This study was aimed at identifying the antibiotic prescription survey in pediatric outpatient prescriptions. This study was carried out in two hospitals namely; Usmanu Danfodiyo University Teaching Hospital, Sokoto, and General Hospital Katsina Nigeria during the period of October to December 2019. A total of 600 prescriptions cumulatively were used as a sample and were selected using the convenience sampling technique. For data collection, a self-designed data collection sheet was used. WHO / INRUD prescribing indicators were used for the analysis of prescription patterns. A total of 600 prescriptions (364 from UDUTHS and 236 from GHKS) were selected and used for the study. Most of the patients admitted to the two selected hospitals were male. The patient’s ages varied from a few months to 12 years, with the majority aged 4 years or less (61.0%) of age. From the 600 prescriptions evaluated, 1564 drugs (912 from UDUTHS and 652 GHKS) were prescribed. The average number of drugs per encounter in UDUTHS and GHKS were 3.0±0.4 and 3.2±0.7 respectively. The percentages of encounters with an antibiotic prescribed in both hospitals were similar: 32.1% for UDUTHS and 31.1% for GHKS. Most antibiotics were targeted at respiratory tract infections Roxithromycin 126 (21.0%) was the most frequently prescribed antibiotic and was prescribed by the proprietary name. This study has revealed inappropriate drug prescriptions in the pediatric outpatient in these hospitals. These include the low rate of prescriptions in generic names; extensive polypharmacy; and inappropriate prescription of antibiotics which could lead to drug-drug interaction and adverse drug reaction is also evident in these hospitals.